Implementasi Kegiatan Got Talent Dalam Mengembangkan Minat Dan Bakat Santri Di Pondok Pesantren Matholi’ul Anwar Simo Sungelebak Karanggeneng Lamongan - fibriani, nofi; wulansari, fira; Agustriya, Sophia; Umami, Riza (Jurnal Murid, 2024)
Every child is born with various potentials and develops according to their talents. An educational institution is a place for channeling students' talents and interests, which are packaged in the form of Got Talent activities. The objectives of this study were (1) to find out how Got Talent activities were implemented and (2) to find out the supporting and inhibiting factors for Got Talent activities in developing interests and talents. This type of research is descriptive qualitative research, which describes the object or subject being studied in absolute terms without being influenced by personal opinions or views. From the results of this study, the implementation of Got Talent activities at the Matholi'ul Anwar Islamic boarding school went very well, and the students were enthusiastic about participating in the Got Talent activities.